On generalized Szasz-Bernstein –Type ‎Operators (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2018)
Resently Dr.R.P. Pathak and Shiv Kumar Sahoo in 2012 intrudes a new modified Szasz-Bernstein –type operators, in the present paper, we introduce generalize Szasz- Bernstein- type operators , we proved that the operators are converge to the function being approximation. In addition, we establish  a Voronovaskaja- type asymptotic formula for this operators